Accumulation patterns of tobacco root allelopathicals across different cropping durations and their correlation with continuous cropping challenges - Zhou, Fangfang; Pan, Yihong; Zhang, Xiaolong; Deng, Guobing; Li, Xiaoting; Xiong, Yubin; Tang, Li (Frontiers in Plant Science, 2024)
Continuous cropping challenges have gradually emerged as pivotal factors limiting the sustainable development of agricultural production. Allelopathicals are considered to be the primary obstacles.However, there is limited information on allelopathic accumulation across various continuous cropping years and its correlation with the associated challenges. Tobacco was subjected to varying planting durations: 1 year (CR), 5 years (CC5), 10 years (CC10), and 15 years (CC15). Our findings unveiled discernible disparities in tobacco growth patterns across diverse continuous cropping periods. Notably, the most pronounced challenges were observed in the CC5 category, characterized by yield reduction, tobacco black shank outbreaks, and a decline in beneficial flora. Conversely, CC15 exhibited a substantial reduction in challenges as the continuous cropping persisted with no significant differences when compared to CR. Within the tobacco rhizosphere, we identified 14 distinct allelopathic compounds, with 10 of these compounds displaying noteworthy variations among the four treatments. Redundancy analysis (RDA) revealed that eight allelopathic compounds exhibited autotoxic effects on tobacco growth, with MA, heptadecanoic acid, and VA ranking as the most potent inhibitors. Interaction network highlighted the pivotal roles of VA and EA in promoting pathogen proliferation and impeding the enrichment of 13 beneficial bacterial genera. Furthermore, a structural equation model elucidated that MA and EA primarily exert direct toxic effects on tobacco, whereas VA fosters pathogen proliferation, inhibits the enrichment of beneficial bacteria, and synergistically exacerbates the challenges associated with continuous cropping alongside EA. These findings suggested discernible disparities in tobacco growth patterns across the various continuous cropping periods. The most pronounced challenges were observed in CC5, whereas CC15 exhibited a substantial reduction in challenges as continuous cropping persisted. VA may play a pivotal role in this phenomenon by interacting with pathogens, beneficial bacterial genera, and EA.